Optimization of Hill Cipher Method for Encryption and Decryption of Prescription Drugs at Puskesmas Twano Jayapura City - Elvis Pawan; Patmawati Hasan (International Journal of Computer and Information System (IJCIS), 2021)
A drug prescription is a written request from a doctor to a pharmacist that must be kept secret because it contains certain doses of drugs and types of drugs that cannot be known by just anyone, especially those who are not interested. From time to time technological advances have a rapid impact on all sectors, both private and government agencies, including the health sector. One form of service in the health sector that can utilize information technology is the manufacture of electronic drug prescriptions that can be sent via an application from a doctor to a pharmacist. The frequent misuse of prescription drugs by unauthorized persons, as well as errors by officers at the pharmacy in reading prescriptions can be fatal for the community, so a solution is needed to overcome this problem. This application is designed using the Hill Cipher Algorithm which is one of the classic types of algorithms in the field of cryptography, but to get the maximum level of security, the algorithm key will be modified using a postal code pattern as a matrix key. Broadly speaking, the Encryption Stage is the first starting from the plaintext which is the type of drug and drug dose, the second key matrix using a POS code pattern, the three plaintexts are converted into blocks, the fourth is arranged into a 2x2 matrix, the fifth is multiplied between the key and the sixth plaintext is multiplied into mod 26 to generate an encrypted ciphertext or recipe. The success rate of system functionality testing using the blackbox method is 100%